Career and College Readiness: A Summary of Two Sessions at the AFB Leadership Conference on Orientation and Mobility and Transition Services for Students with Visual Impairments. (March 2019) - Danaher, Shelley
Editor's Note: This commentary is based on the conference sessions, "Orientation and Mobility Career, College and Community Readiness Standards, " by Kathryn Botsford and Mary Tellefson, and "Engaging Students, Families and Teams for Success After High School, " by Sheila Koenig, which took place on Thursday, February 28, 2019, and Friday, March 1, 2019, respectively, at the American Foundation for the Blind Leadership Conference in Arlington, VA.